KEPEMIMPINAN TRANSFORMASIONAL, WORK LIFE BALANCE, DAN KOMUNIKASI TERHADAP KINERJA KARYAWAN PADA PT. KANMO GROUP - Mulyadi, Made; Rahayu Candra Dewi, Ni Made; Rasmen Adi, I Nyoman; Gede Elvina Adi Saputri, Luh (CV. Lafadz Jaya, 2024)
This research uses a saturated sampling technique. Saturated sampling is a sample selection technique when all members of the population are used as samples. The types of data used are quantitative and qualitative data. The data analysis technique used in this research is the multiple linear regression analysis method, carried out using the SPSS program. The results of this research show that transformational leadership has a positive effect on employee performance. Work life balance has a positive effect on employee performance. Communication has a positive effect on employee performance. Transformational leadership, work life balance, and communication simultaneously influence employee performance. This means that the better the implementation of transformational leadership in the company, accompanied by a good work life balance, and the company has good communication between colleagues and superiors, the more employee performance will be able to improve. Suggestions for further research are recommended to look for larger companies with a wider range of respondents so that they can provide a more real picture of what is happening in the field and future researchers are expected to use different variables or add independent variables that can influence employee performance such as work environment and organizational culture.